Modelling of alluvial soil quality and production in permanent banana Harton plantations - Nelino Florida Rofner; Cesar Augusto Gozme Sulca; Alex Rengifo Rojas (Soil and Water Research, 2023)
Plantain is the most important crop for the Peruvian Amazonian population, developed in recent alluvial soils rich in nutrients, but fragile and susceptible to degradation. Therefore, the impact of permanent cultivation was evaluated, through modelling, on indicators of recent alluvial soil quality and production in plantations of Musa paradisiaca L. var. Harton, in the Aguaytia River valley, Peru. The treatments were areas with permanent plantain plantations of 2 (T0), 15 (T1), 4 (T2), and 5 (T3) years of management, evaluating soil physicochemical indicators and plantain production indicators. The results show significant differences for all yield and soil indicators evaluated, except for bulk density (Bd), clay fraction, soil organic matter (OM) and N. The modelling determined a significant positive impact on Bd and a significant negative impact on pH, P, pseudostem diameter and height, commercial fingers and bunch weight. In conclusion, the modelling shows trends of quality and yield reduction in 15 years of permanent management of plantain Var. Harton, and compromises the sustainability of the agroecosystem in the medium term.